THE EFFECT OF GENDER DIVERSITY AND FINANCIAL RATIOS ON FINANCIAL DISTRESS IN MANUFACTURING COMPANIES INDONESIA - Rita Tri Ariska; Mohammad Arief; Prasetyono Prasetyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of gender diversity and financial ratios on financial distress. The data used in this study are secondary data. The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period with a purposive sampling technique. The number of data on manufacturing companies is as many as 141 companies, but there are only 94 companies that fall into the research criteria. The analytical method used is Logistic Regression Analysis. Based on the research results, gender diversity, net profit margin, current ratio, and debt ratio have no effect on financial distress, return on assets has a negative effect on financial distress, and working capital to total assets has a positive effect on financial distress